ETIKA JURNALISTIK PENGGUNAAN CLICKBAIT OLEH VODCAST DEDDY CORBUZIER DALAM MENGEMAS ISU SEKSUALITAS - Putri Mastura, Ferla; Utami, Dewi; Lukitowati, Suci (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
This study aims to determine the journalistic ethics of using clickbait by vodcaster Deddy Corbuzier in packaging issues of sexuality. This research was conducted through a qualitative descriptive type approach by identifying the use of clickbait based on the type of clickbait concept according to Biyani, Tsioutsiouliktis, and Blackmer (2016). These types consist of exaggeration, teasing, inflammatory, formatting, graphic, bait and switch, ambiguous and wrong. More than that, this study also identified the dimensions of sexuality according to Argyo Demartoto (2010). In analyzing clickbait practices that indicate a violation of journalistic ethics, the concept of journalistic ethics is used in the book The Elements of Journalism by Bill Kovach and Tom Rosenstiel (2007). Of the ten elements of journalism, there are five elements that are most closely related and become the main subject of research, including: first, obligation to truth, second, first loyalty to citizens, third, verification discipline, fourth, trying to make information interesting and relevant, finally, being able to maintain information that is made comprehensively and proportionately. The results of the study show that the practice of clickbait carried out by #CloseTheDoor Corbuzier Podcast has proven to injure a number of elements of journalistic ethics. This is proven based on the results of observations and interviews with research informants.